Angiotensin converting enzyme inhibitors: Scientific basics for clinical use (New York A John Wily & Sons, 1992)
This quick reference guide has been designed for clinicians prescribing the use of angiotensin converting enzyme (ACE) inhibitors. The text has been updated to highlight new research discoveries, such as the role of ACE inhibitors in preventing the development of overt heart failure.
Keywords: Angiotensin converting enzyme -- Inhibitors -- Therapeutic use; Hypertension -- Chemotherapy; Kidneys -- Diseases -- Chemotherapy